Patterns of negotiation of meaning routine in online forum discussion - Abdul Karim, Noor Mazni; Abdul Ghani, Rozina; Ahamad Shah, Mohamed Ismail (Universiti Putra Malaysia, 2017)
This study examines a text-based, asynchronous online forum discussion among English language teacher trainers who were involved in a two-week online professional development course. It investigates the participants’ negotiation of meaning routine when they come across new content related item and describes the pattern of this negotiation of meaning routine. A textual analysis method, employing Smith’s (2003) expansion of Varonis and Gass Model (1985) for negotiation of meaning, was utilised to analyse the discussion threads. The analysis revealed that the participants did engage in negotiation of meaning and all the four negotiation of meaning steps (trigger, indicator, response and reply to response) were evident. It was also revealed that content triggers, local indicator, elaboration in responses and task appropriate response were frequently used. As the application of CMD for teaching and learning is increasing, findings of this study could inform educators about the kind of strategies that could enrich online interaction.